The professionalisation of auditing in less developed countries: the case of Sri Lanka. Issue 4 (4th April 2017) - Yapa, Prem W.S.; Ukwatte Jalathge, Sarath L.; Siriwardhane, Pavithra
Abstract : Purpose: This paper aims to examine the tensions amongst the audit firms operating in Sri Lanka with the introduction of open economic policies in early 1980s and its impact to the auditing profession. Design/methodology/approach: Using a qualitative approach, this study consists of in-depth interviews, documentary review and critical interpretation supported by the perspectives of globalisation, digitalisation and neo-liberalism. Findings: The findings indicate that the main reasons for the tension between audit firms (local and international) have been the conflict of interests on the market share. While global pressures on International Standards of Auditing created more opportunities for international audit firms to capture a wider market with the support of the state, the local audit firms apparently lost their market and experienced tension created by staff. Evidence shows the negative impact of globalisation on the open economic policies and the local audit market. Research limitations/implications: The findings of this research will be useful for policymakers in revising auditing practices to ensure healthy corporate governance. Only 25 interviews were conducted; hence, the results may not be a holistic representation of the audit environment in Sri Lanka. Originality/value: This study is significant, as the business capital has surged into Sri Lankan market as a result of the ongoing international agencies-led economic reforms. Such reforms have emphasised the transparency and accountability.